Features of hemodynamic and immunological parameters in patients with recurrent uveitis complicated by hypertension, Fuchs heterochromic uveitis and Posner-Schlossman syndrome - Храменко, Наталія Іванівна; Величко, Людмила Миколаївна; Коновалова, Наталія Валеріївна; Богданова, Олександра Вікторівна (My University, 2023)
Introduction: Uveitis is a disease that manifests with increased vascular permeability and occlusion, with some ischemia and inflammatory mediators. It is characterized by a wide range of pathological processes, including inflammation, increased vascular permeability and occlusion, local ischemia and cell alteration by inflammatory mediators, and is characterized by the presence of complications. Aim: To study the state of ocular hemodynamics by rheoophthalmography, as well as the immune status in patients with idiopathic recurrent anterior uveitis complicated by intraocular hypertension, Fuchs heterochromic uveitis, Posner-Schlossman syndrome, during the relapse period. Materials and methods: 93 patients with idiopathic recurrent anterior uveitis were included in this study, 8 patients with Fuchs' uveitis, and 6 patients with Posner-Schlossman syndrome. According to clinical signs, relapse and remission were considered. The control group (healthy volunteers of the same age) consisted of 27 people. In this regard, 5 groups of subjects were formed. The mean age of the patients was (M ± SD) 39.2 ± 14.6 years. According to the Median (range), the duration of the disease in patients was 2033 (350-3285) days, intraocular hypertension being recorded at P0 > 20 mm Hg. Statistical analysis was carried out in spreadsheets using STATISTICA 8.0 (StatSoft.Inc) program. Quantitative indicators were evaluated according to the correspondence to the normal distribution and to the Kolmogorov-Smirnov criterion. With a normal distribution, arithmetic means (M) and standard deviations (SD), limits of the 95% confidence interval (95% CI) and Student's t-test were calculated. Results: The volumetric blood filling of the eye according to the rheoophthalmographic indicator RQ during the period of remission of uncomplicated and complicated by hypertension anterior uveitis was reduced by 32.4%-40.5%, respectively, compared with the norm. During the period of relapse, RQ was significantly higher by 28% (p<0.05) than in remission, in the group of uncomplicated uveitis, and in the group of uveitis with increased IOP, no significant differences between the periods of remission and relapse were observed, which reflected the ischemic process in the relapse period. Volumetric blood filling in Fuchs and Posner-Schlossman syndromes in the acute period did not differ from the norm. Cellular immunity in the groups of uncomplicated and complicated by intraocular hypertension idiopathic uveitis, as well as with Fuchs and Posner-Schlossman syndromes, had a higher level of CD4 helper lymphocytes and a lower level of CD8 suppressor lymphocytes, which reflected higher values of the immunoregulatory index. The increase in the immunoregulatory index is most pronounced in Fuchs and Posner-Schlossman syndromes. Discussion: In the presented study, the incidence of idiopathic recurrent anterior uveitis complicated by intraocular hypertension was 9,9% among all cases of idiopathic recurrent anterior uveitis in one-time period. According to literature, this complicated form of uveitis occurs in 11,5%-46,1% of cases. Most often (up to 92% of cases), the anterior chamber angle was open. Conclusions: Different activity of the mechanisms regulating the balance of cellular and humoral immunity, sensitivity of T-cells to eye antigens in idiopathic anterior uveitis, Fuchs and Posner-Schlossman syndromes was assumed. Peculiarities of eye hemodynamics in these forms of uveitis were also revealed. Abbreviations: IOP = intraocular pressure, IOHS = inflammatory ocular hypertension syndrome, HSV = herpes simplex virus, CMV = cytomegalovirus, OCT = optical coherence tomography, OD = right eye, OS = left eye.
Keywords: Fuchs syndrome; Posner-Schlossman syndrome; T-cell sensitivity to eye antigens; eye hemodynamics; idiopathic anterior uveitis